2010
DOI: 10.1186/1471-2350-11-161
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of DC-SIGN promoter indicates an association between promoter variation and risk of nasopharyngeal carcinoma in cantonese

Abstract: BackgroundThe dendritic cell-specific intercellular adhesion molecule 3 grabbing non-integrin (DC-SIGN) is an important pathogen recognition receptor of the innate immune system. DC-SIGN promoter variants play important role in the susceptibility to various infectious diseases. Nasopharyngeal carcinoma (NPC) is a malignancy that is common in southern China and whether DC-SIGN promoter variants have effects on susceptibility to NPC is still unknown. The aim of this study is to ascertain the potential involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 54 publications
1
18
2
Order By: Relevance
“…EBV has been observed to infect DC-SIGN−positive cells such as immature DCs, monocytes and some macrophages (Li et al 2002; Severa et al 2012). The only study investigating the association of polymorphisms of CD209 with NPC risk is a study by Xu et al (2010). They investigated SNPs in the promoter and found that the GG genotype of rs2287886, the AA genotype of rs735240, and the G allele of rs735239 were associated with an increased NPC risk.…”
Section: Discussionmentioning
confidence: 99%
“…EBV has been observed to infect DC-SIGN−positive cells such as immature DCs, monocytes and some macrophages (Li et al 2002; Severa et al 2012). The only study investigating the association of polymorphisms of CD209 with NPC risk is a study by Xu et al (2010). They investigated SNPs in the promoter and found that the GG genotype of rs2287886, the AA genotype of rs735240, and the G allele of rs735239 were associated with an increased NPC risk.…”
Section: Discussionmentioning
confidence: 99%
“…The Scientific World Journal [27][28][29], further investigation into other candidate SNPs contributing to KD morbidity is needed. Besides dendritic cells, IVIG was observed to affect many other cells, including endothelial cells, monocytes, neutrophils, and T and B cells [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its location, it is feasible that this single nucleotide polymorphism may alter the regulatory binding sequence and influence mRNA expression. 15 The only study investigating the association of polymorphisms of genes encoding C-type lectin receptors and RIG-I-like receptors with cancer risk is a study by Xu et al 16 They investigated single nucleotide polymorphisms of the CD209 gene and found that the GG genotype of the rs2287886, AA genotype of the −939 promoter polymorphism, and the G allele of the rs735239 single nucleotide polymorphism were connected with higher nasopharyngeal carcinoma risk. 16 Polymorphisms in the promoter of the CD209 gene and in the CD209 gene were also associated with hemorrhage in patients with dengue fever (G allele of rs4804803), 17,18 modulated tuberculosis risk (G allele of rs4804803, A allele of rs735239), [19][20][21] higher celiac disease risk in HLA-DQ2-negative cases (G allele of rs4804803), 22 increased ulcerative colitis risk in HLA-DR3-positive patients (G allele of rs4804803), 23 higher susceptibility to cytomegalovirus infection (G allele of rs735240 and C allele of rs2287886), 24 protection from lung cavitation 20 and fever during tuberculosis 25 (GG genotype and G allele of rs4804803), decreased HIV-1 infection risk (GG genotype of rs4804803), 21 accelerated progression to acquired immune deficiency syndrome in HIV-1-infected hemophiliacs (C allele of rs2287886), 26 decreased human T-lymphotropic virus type I infection risk (G allele of rs4804803, A allele of rs2287886), 27 increased severity of liver disease during hepatitis C virus infection (G allele of rs4804803), 28 and better prognosis following severe acute respiratory syndrome (G allele of rs4804803).…”
Section: Second Premise: Polymorphisms Affecting Functionmentioning
confidence: 99%
“…15 The only study investigating the association of polymorphisms of genes encoding C-type lectin receptors and RIG-I-like receptors with cancer risk is a study by Xu et al 16 They investigated single nucleotide polymorphisms of the CD209 gene and found that the GG genotype of the rs2287886, AA genotype of the −939 promoter polymorphism, and the G allele of the rs735239 single nucleotide polymorphism were connected with higher nasopharyngeal carcinoma risk. 16 Polymorphisms in the promoter of the CD209 gene and in the CD209 gene were also associated with hemorrhage in patients with dengue fever (G allele of rs4804803), 17,18 modulated tuberculosis risk (G allele of rs4804803, A allele of rs735239), [19][20][21] higher celiac disease risk in HLA-DQ2-negative cases (G allele of rs4804803), 22 increased ulcerative colitis risk in HLA-DR3-positive patients (G allele of rs4804803), 23 higher susceptibility to cytomegalovirus infection (G allele of rs735240 and C allele of rs2287886), 24 protection from lung cavitation 20 and fever during tuberculosis 25 (GG genotype and G allele of rs4804803), decreased HIV-1 infection risk (GG genotype of rs4804803), 21 accelerated progression to acquired immune deficiency syndrome in HIV-1-infected hemophiliacs (C allele of rs2287886), 26 decreased human T-lymphotropic virus type I infection risk (G allele of rs4804803, A allele of rs2287886), 27 increased severity of liver disease during hepatitis C virus infection (G allele of rs4804803), 28 and better prognosis following severe acute respiratory syndrome (G allele of rs4804803). 29,30 It was shown that the A allele of the rs4804803 single nucleotide polymorphism may increase gene expression in vitro, 17 Abbreviations: SNP, single nucleotide polymorphism; OR, odds ratio; CI, confidence interval; MRC, mannose receptor C; CD, cluster of differentiation; NPC, nasopharyngeal carcinoma; DC-SIGN, dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin; TNF, tumor necrosis factor; IL, interleukin; IP, interferon-gamma inducible protein 10; HIV, human immunodeficiency virus; AIDS, acquired immunodeficiency virus; HTLV, human T-cell lymphotropic virus; HCV, hepatitis C virus; SARS, severe acute respiratory syndrome; LDH, lactate dehydrogenase; Sp, specificity protein; AP, activator protein; CLEC, C-type lectin domain, the next number is the family number 7, the next letter is the letter of family member; TLR, toll-like receptor; PBMC, peripheral blood mononuclear cell; IFN, interferon; RIG-I, retinoic acid-inducible gene I; GM-CSF, granulocyte-macrophage colony-stimulating factor; MAvS/vISA/IPS-1, mitocho...…”
Section: Second Premise: Polymorphisms Affecting Functionmentioning
confidence: 99%